Mental privacy and equity in cognitive enhancement. Challenges and perspectives from the Spanish and Chilean legal framework - Intxaurtieta Zubizarreta , Antón (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2024)
The challenges posed by the advance and development of disruptive technologies have energized the activity of the legislator, demanding new responses and guarantees to already known legal assets. This is now the case of privacy of thought and equality between persons, which have led to the birth of new rights such as mental privacy or the right to equal access to cognitive augmentation. This article will study both rights and how they fit into both the Spanish and Chilean legal systems. The latter is especially relevant because it is the first legal system to regulate neuro-rights.
Keywords: neurotechnology; mental privacy; neurodata; cognitive enhancement; therapy